Adipose tissue-derived exosomes contribute to obesity-associated liver diseases in long-term high-fat diet-fed mice, but not in short-term - Son, Taesang; Jeong, Inae; Park, Jeongjin; Jun, Woojin; Kim, Andre; Kim, Ok-Kyung (Frontiers in Nutrition, 2023)
Our study aimed to investigate the changes in hepatic endoplasmic reticulum (ER) stress, inflammation, insulin signaling, and lipid metabolism during the administration of a high-fat diet (HFD) in mice in order to identify correlations between obesity and metabolic disease development in the liver. We used short-, medium-, and long-term HFD periods, corresponding to 4, 8, and 12 weeks, respectively, and isolated exosomes from adipose tissue. We confirmed the effect of adipose tissue-derived exosomes on metabolic disorders in obesity in alpha mouse liver 12 (AML12) hepatocytes. Adipose tissue-derived exosomes from HFD mice did not affect the AML12 cells after 4 weeks, but ER stress, inflammatory response, insulin resistance, and lipid synthesis were observed after 8 and 12 weeks. Furthermore, we confirmed that an HFD increases the amount of adipose tissue-derived exosomes in mice. Consequently, we can infer that adipose tissue-derived exosomes from HFD-fed mice significantly increase ER stress, inflammatory response, insulin resistance, and lipid synthesis in AML12 cells. Our results demonstrate that obesity alters the effects of adipose tissue-derived exosomes in the liver, potentially becoming a risk factor in the development of obesity-induced liver diseases.